INVESTIGATION OF THE ABSORBING CAPACITY OF PLANTS UNDER CONDITIONS OF STRESSOR IMPACT BY THE RESIDUAL RADIOACTIVITY METHOD - Тихенко, О.М.; Міхєєв, О.М. (Proceedings of National Aviation University (archive), 2012)
The aim of work has been the investigation of UV-radiation influence on the absorbing capacity of plant objects in relation to radionuclide using the new method of biological objects state registration under the conditions of stressor impact – the residual radioactivity method, that is based on measuring absorption of potassium chemical analog – caesium-137, that is brought in chloride compound into cultural medium. As a result of conducted investigation, the prognostic potential of the residual radioactivity method has been estimated. There have been determined, first, that the method could to be used in the form of impulse sprout incubation with radiotracer, second, it has to be taken into account that inhibition of absorbing capacity by certain stressor dose occurs two days earlier than the state of plant activity inhibition is fixed.